Research on Mechanisms and Control Measures of Surrounding Rock Disaster in Large Section Roadway with Top Coal under the Influence of Tectonic Stress - Yang Yu; Jianfei Lu; Dingchao Chen; Yuxin Pan; Xiangqian Zhao; Cheng Chen (Shock and Vibration)
Based on the research background of large section roadway with top coal (LSRTC) in thick coal seam mining in Wangzhuang Coal Mine, Shanxi Province, China, catastrophe characteristics of the surrounding rock of the LSRTC were investigated and summarized. Based on the principle of damage mechanics, the critical size discriminant of the LSRTC was deduced, and the induction mechanism of section size effect and tectonic stress effect on the roadway surrounding rock disaster was revealed. Accordingly, the roadway surrounding rock control principle with the basic idea of “stabilizing and controlling top coal, reconstructing the coal wall, and limiting floor heave” was put forward, and the roadway surrounding rock stability control countermeasures with the core technology of “strong pressure support for roof + grouting reinforcement for two sides + bolt barrier for floor angle” were developed, which solved the surrounding rock control problem of the LSRTC under the action of tectonic stress and provided a useful reference for the difficult problem of roadway surrounding rock control under similar conditions.